2012
DOI: 10.1371/journal.pone.0040776
|View full text |Cite
|
Sign up to set email alerts
|

The Pharmacological Chaperone AT2220 Increases Recombinant Human Acid α-Glucosidase Uptake and Glycogen Reduction in a Mouse Model of Pompe Disease

Abstract: Pompe disease is an inherited lysosomal storage disease that results from a deficiency in the enzyme acid α-glucosidase (GAA), and is characterized by progressive accumulation of lysosomal glycogen primarily in heart and skeletal muscles. Recombinant human GAA (rhGAA) is the only approved enzyme replacement therapy (ERT) available for the treatment of Pompe disease. Although rhGAA has been shown to slow disease progression and improve some of the pathophysiogical manifestations, the infused enzyme tends to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 48 publications
3
73
0
Order By: Relevance
“…These data taken together suggest that the blood flow towards the skeletal muscles may not be the limiting factor for the effective delivery/action of the recombinant enzyme to the skeletal muscles and the enhancement of their functional capacity. Indeed, other factors such as the stability of the recombinant enzyme at body pH and temperature, seem to affect its effectiveness in target tissues [13]. Nevertheless, the present study does not provide insights to the mechanisms of the recombinant enzyme delivery/action to the skeletal muscles.…”
Section: Discussionmentioning
confidence: 75%
“…These data taken together suggest that the blood flow towards the skeletal muscles may not be the limiting factor for the effective delivery/action of the recombinant enzyme to the skeletal muscles and the enhancement of their functional capacity. Indeed, other factors such as the stability of the recombinant enzyme at body pH and temperature, seem to affect its effectiveness in target tissues [13]. Nevertheless, the present study does not provide insights to the mechanisms of the recombinant enzyme delivery/action to the skeletal muscles.…”
Section: Discussionmentioning
confidence: 75%
“…Although pharmacological chaperone therapy (PCT) has been developed as a strategy to rescue mutant enzymes from degradation, recent studies showed that chaperones are also able to enhance physical stability and potentiate the therapeutic action of the enzymes used for ERT (40)(41)(42)(43). These studies, performed in cell systems and in the animal models of Pompe and Fabry disease, suggested a major change in the use of PCT.…”
Section: Combination Of Chaperones and Ertmentioning
confidence: 99%
“…In addition, a small molecule chaperone that improves the stability of the enzyme and enhances glycogen clearance in Pompe mice is being tested clinically. 14 Gene therapy with recombinant AAV vectors encoding GAA is also being evaluated. 15,16 Substrate reduction that abates the production of glycogen represents another therapeutic strategy for lysosomal storage disorders.…”
Section: Introductionmentioning
confidence: 99%